Mechanisms and Pathways through which Digital Infrastructure Aid Empowers the Economic Resilience of Recipient Countries (Journal of economic and management development research, 2026)
With the acceleration of global digitalization, digital infrastructure has become a pivotal factor in fostering the economic resilience of developing countries. This study explores the mechanisms through which digital infrastructure aid enhances the economic resilience of recipient countries and analyzes the specific pathways for implementing these mechanisms. The research suggests that digital infrastructure can help recipient countries better cope with external shocks and achieve sustainable economic development by boosting productivity, facilitating information flow, stimulating enterprise growth, and improving social welfare. To achieve these goals, the study proposes pathways such as policy support, financial investment, technology transfer, cross-border cooperation, and localized implementation to maximize the enabling effects of digital infrastructure aid, thereby strengthening the economic resilience of recipient countries.
Keywords: Digital infrastructure; Economic resilience; Foreign aid; Technological innovation